2014
DOI: 10.1152/ajpendo.00002.2014
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα regulates macrophage activation and systemic metabolism

Abstract: /EBP␣ regulates macrophage activation and systemic metabolism. Am J Physiol Endocrinol Metab 306: E1144 -E1154, 2014. First published April 1, 2014; doi:10.1152/ajpendo.00002.2014.-Macrophage infiltration plays an important role in obesity-induced insulin resistance. CCAAT enhancerbinding protein-␣ (C/EBP␣) is a transcription factor that is highly expressed in macrophages. To examine the roles of C/EBP␣ in regulating macrophage functions and energy homeostasis, macrophage-specific C/EBP␣ knockout (M␣KO) mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 41 publications
1
39
0
Order By: Relevance
“…The defects we observed in JUNB-deficient macrophages included altered transcription of a subset of immune-related genes, decreased secretion of M(LPS)-associated cytokines in response to TLR ligands, and weakened M(IL-4) polarization following treatment with IL-4. It is notable that JUNB positively regulates both M(LPS) and M(IL-4) activation, since to our knowledge, virtually all previously described transcription factors with demonstrated roles in macrophage polarization specifically promote either M(LPS) or M(IL-4) activation, with the exception of C/EBPα (38). Importantly, at baseline, Junb Δ Lyz2 mice exhibit no gross defects in survival or development, suggesting that deletion of JUNB does not disrupt the homeostatic functions of monocytes and tissue macrophages but specifically affects activation.…”
Section: Discussionmentioning
confidence: 93%
“…The defects we observed in JUNB-deficient macrophages included altered transcription of a subset of immune-related genes, decreased secretion of M(LPS)-associated cytokines in response to TLR ligands, and weakened M(IL-4) polarization following treatment with IL-4. It is notable that JUNB positively regulates both M(LPS) and M(IL-4) activation, since to our knowledge, virtually all previously described transcription factors with demonstrated roles in macrophage polarization specifically promote either M(LPS) or M(IL-4) activation, with the exception of C/EBPα (38). Importantly, at baseline, Junb Δ Lyz2 mice exhibit no gross defects in survival or development, suggesting that deletion of JUNB does not disrupt the homeostatic functions of monocytes and tissue macrophages but specifically affects activation.…”
Section: Discussionmentioning
confidence: 93%
“…The expression of PPARγ and C/EBPα in mice and in adipocytes (3T3‐L1 cells) by curcumin improved insulin resistance, glucose uptake (Pan et al, ), lipolysis of circulating TGs, and their storage in adipose tissue (Kim et al, ; B. Lee et al, ). But a dose of curcumin is important for upregulating the protein expression of PPARγ and C/EBPα in adipocytes, and a high dose of curcumin was ineffective in the adipocyte (Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Kang and colleagues found that IL-32 induced IL-10 expression by suppressing C/EBPαbinding to IL-10 promoter and suggested that C/EBPα DNA binding negatively regulates IL-10 expression (43). In a recent study using a myeloid specific C/EBPαknockout model, Lee and coworkers showed that in C/EBPα-deficient macrophages, IL-10 levels were reduced in response to M2 differentiation stimulus IL-4, but were unchanged in white fat tissue, as compared to wild type counterparts (77), suggesting tissue-specific and differential ways of regulation of IL-10 by C/EBPα.…”
Section: Discussionmentioning
confidence: 99%